EFEKTIVITAS PENYELENGGARAAN E-GOVERNMENT PADA BADAN PELAYANAN PERIZINAN TERPADU KOTA MALANG - Sudrajat, Raharwindy Kharisma (Jurnal Administrasi Publik, 2015)
Abstract: The Effectiveness Of The Implementation Of E-Government Program Integrated Permit Service Malang City. Traditional government identical with long queues and maladministration the demands of the transformation of the bureaucracy of government to develop electronic government. Although the government has developed a new program to improve service, there are always many problems which occurs both in the sphere of internal or the community. The type of research that is used in this study is the type of research descriptive with a qualitative approach while data collection techniques conducted through interviews , observation , and documentation of using data analysis model interactive Miles and Huberman (2013,h.31-32). The the study results of the effectiveness of the implementation of e-government program on a institution of service integrated permit handling Malang City is quite effective if the purpose of which the convention of e-government program adapted to the purpose of e-government program national of President Instruction no 3 in 2003 about policy and national strategy the development of e-government program. The barrier is the licensing on integrated permit handling services agency Malng City is still conventional spring, there was no legal provision regarding the e-government program at Malng City And still lack of appropriate infrastructure that supports and free of charge to the community in implementing the e-government program On a body of service integrated permit handling the Malang City. Keywords: performance appraisal, Civil Servant Abstrak: Efektivitas Penyelenggaraan E-Government Pada Badan Pelayanan Perizinan Terpadu Kota Malang. Traditional government yang identik dengan antrian yang panjang dan juga maladministration sehingga menuntut adanya transformasi birokrasi pemerintahan untuk mengembangkan electronic government. Walaupun pemerintah selalu mengembangkan program baru untuk memperbaiki pelayanan, tetap selalu ada permasalahan yang terjadi baik di lingkup internal maupun dari masyarakat. Jenis penelitian yang digunakan didalam penelitian ini adalah jenis penelitian deskriptif dengan pendekatan kualitatif sedangkan teknik pengumpulan data dilakukan melalui wawancara, observasi, dan dokumentasi dengan menggunakan analisis data model Interaktif Miles (2013, h.31-32). Hasil penelitian dari efektivitas penyelenggaraan e-Government pada Badan Pelayanan Perizinan Terpadu Kota Malang sudah cukup efektif bila mana tujuan dari diselenggarakannya e-Government disesuaikan dengan tujuan e-Government nasional Inpres No. 3 Tahun 2003 tentang Kebijakan dan Strategi Nasional Pengembangan e-Government. Faktor penghambat yaitu penyelenggaraan perizinan pada Badan Pelayanan Perizinan Terpadu Kota Malang masih semi konvensional, belum ada ketetapan hukum berkaitan dengan e-Government di Kota Malang dan masih kurang lengkapnya infrastruktur yang menunjang dan gratis untuk masyarakat dalam menyelengarakannya e-Government pada Badan Pelayanan Perizinan terpadu Kota Malang. Kata kunci: Efektivitas, e-Government, Badan Pelayanan Perizinan Terpadu Kota Malang